Impact of Viral Advertising on Product Promotion : An Experimental Study - Kaur, Balpreet; Sharma, Rishi Raj (Indian Journal of Marketing, 2018)
The study assessed the impact of viral advertising on product promotion. For this, an experimental study was first conducted to assess the effectiveness of a viral advertisement of Amway products (home, beauty, and nutrition) which was liked and shared maximum number of times over the Internet. For the purpose, one-group pretest - post test research was undertaken. The advertisement was shown to 450 respondents belonging to Punjab. The responses (before & after watching the advertisement) were evaluated using McNemar test. The results revealed that the viral advertisement of Amway products, selected for purpose of experimentation, became successful in generating awareness among the respondents towards the brand and the number of respondents who were aware of Amway products increased significantly after watching the ad. Moreover, the ad also had a significant impact on purchase intentions of the respondents. Those who were not interested in buying the Amway products changed their intentions after watching the advertisement. As far as dissemination behavior of the respondents is concerned, 'perceived quality of products in the video' and 'multimedia effect' were found as the two main factors (ranked 1st and 2nd, respectively) inducing the participants to forward the video of Amway products. To generalize the results pertaining to viral advertisements of brands, a second study was conducted on the same set of respondents to explore general factors which motivated them to share viral advertisements on YouTube, social networking sites, etc. These factors included Content of the Video & Feel Good Factor, Intellectual Stimuli, Multimedia Effect & Simplicity of Task, and Concern for Society. Among these factors, the factor : Multimedia Effect & Simplicity of Task had the highest mean score. However, the major findings of both the studies were similar, suggesting some important implications for marketers.